Agenda Lanjutan Pasca Institusionalisasi Zakat - Arif Hartono (Unisia, 2000)
The obligation of zakat has special characteristic in Islam. Except as a way to obey and to play the religion rule, zakat also has the economical implication. Except as an individual compulsory, zakat also has the social implication. By legalized Ordinance number 38/1999 about management of zakat, it is hoped that the advantage of zakat can be more optimal. But, that ordinance should be followed by the others agenda, politically or economically, as the implication of the use of that ordinance.